2015
DOI: 10.1007/s12185-015-1918-6
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming immunoregulatory plasticity of mesenchymal stem cells for accelerated clinical applications

Abstract: we discuss novel strategic approaches that enhance the therapeutic potential of MSCs through a consideration of MSC plasticity in immune modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 57 publications
0
34
1
1
Order By: Relevance
“…As already mentioned, because of the capability of MSCs to differentiate into several lineages, including chondrocytes, adipocytes and osteoblasts, as well as their role in tissue repair and their ability to home to the site of injury after systemic administration, several clinical trials for a wide range of diseases have been reported and are ongoing (Mahmood et al, 2003; Barry and Murphy, 2004; Steinert et al, 2012; Madrigal et al, 2014; Kim and Cho, 2015; Seebach et al, 2015). We extensively studied the FVV construct FV.U3-IL1RA-EGFP (NA1) compared to a FV.U3-EGFP (MD09) control vector in their ability to transduce mesenchymal cell lines and primary MSCs ( Figure 3 ) and provide sustained long-term transgene expression in primary MSCs over a time period of 137 days which is noticeable ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, because of the capability of MSCs to differentiate into several lineages, including chondrocytes, adipocytes and osteoblasts, as well as their role in tissue repair and their ability to home to the site of injury after systemic administration, several clinical trials for a wide range of diseases have been reported and are ongoing (Mahmood et al, 2003; Barry and Murphy, 2004; Steinert et al, 2012; Madrigal et al, 2014; Kim and Cho, 2015; Seebach et al, 2015). We extensively studied the FVV construct FV.U3-IL1RA-EGFP (NA1) compared to a FV.U3-EGFP (MD09) control vector in their ability to transduce mesenchymal cell lines and primary MSCs ( Figure 3 ) and provide sustained long-term transgene expression in primary MSCs over a time period of 137 days which is noticeable ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have capacity of self-renewal and multi-lineage differentiation to form mesodermal, ectodermal and endodermal tissues, including the bone, muscle, neurons, hepatocytes and skin1. MSCs can promote angiogenesis and differentiate into insulin producing cells23.…”
mentioning
confidence: 99%
“…Intriguingly, the in vitro pre-activation of MSCs (priming) holds promise as an interesting process for improving MSCs-immunomodulatory effects, thus conferring therapeutic advantages. However, a high diversity in the outcomes of clinical trials, using MSCs for treating different diseases, has been reported [9]. This variation remains vague since a complete mechanistic understanding of MSCs-mediated immunomodulation is still lacking.…”
Section: Introductionmentioning
confidence: 99%